Relationship of critical speed derived from a 10-min submaximal treadmill test to 5-km and 10-km running performances - Follador, L.; de Borba, E. F.; da Silva, S. G. (Applied Physiology, Nutrition, and Metabolism, 2022)
It has been shown that the critical speed (CS) predicted from a perceptually self-regulated 10-min submaximal treadmill test (T10) is reliable and closely matches the CS estimated from conventional methods. To assess the relationship between the T10 and 5-km and 10-km running performances, 36 recreational runners (mean SD: age: 32.2 ± 6.2 years, height: 173.2 ± 7.3 cm, weight: 70.9 ± 8.8 kg, maximal oxygen uptake (V?O2max): 53.3 ± 6.1 mL·kg-1·min-1) performed a ramp incremental test and 2 T10 tests (the first as a familiarization trial). Results showed that the T10 CS (3.9 ± 0.44 m·s-1) was significantly correlated with runners` last 6 months best performances in 5 km (20.3 ± 2.7 min; r = -0.90) and 10 km (42.7 ± 5.7 min; r = -0.91), the V?O2max (r = 0.75), the speed associated with the gas exchange threshold (vGET: 3.38 ± 0.36 m·s-1; r = 0.76), the speed associated with the second ventilatory threshold (vVT2: 4.15 ± 0.49 m·s-1; r = 0.84), and the speed associated with the V?O2max (vV?O2max: 4.78 ± 0.54 m·s-1; r = 0.87). Moreover, 79% and 83% of the variance in 5-km and 10-km performances could be explained solely by the CS predicted from the T10. Results evidenced the strong relationship and practical performance relevance of the T10 CS test. Novelty: • Critical speed derived from a 10-min submaximal treadmill test (T10) is significantly correlated with 5-km and 10-km running performances. • The T10 critical speed test may represent a useful tool for assessing running performance capabilities.